The taxonomy of Heteropanope indica De Man, 1887 from the Indian Ocean, with a note on Pilumnopeus pearsei (Rathbun, 1932) (Crustacea: Decapoda: Brachyura: Pilumnidae) - Patel, Krupal; Trivedi, Jigneshkumar; Mitra, Santanu; Ng, Peter K. L. (Zootaxa, 2024)
Benthopanope indica (De Man, 1887) was originally described from the Mergui Archipelago and has subsequently been reported from many Indo-West Pacific localities. The identity of this species is herein clarified. The re-examination of the type female, fresh specimens collected from Chilika Lake, Odisha State, India, as well as material from other locations, revealed that B. indica is not a Benthopanope species but should be assigned to Pilumnopeus instead. Pilumnopeus indicus comb. nov. is now restricted to the Indian Ocean and is reported from the western coast of Peninsular Malaysia for the first time. Heteropanope pearsei Rathbun, 1932, described from East Asia, previously synonymised under P. indicus by Sakai (1965), is here shown to be valid species of Pilumnopeus, and all previous records of “B. indica” from Japan, China, Taiwan, and Korea must be referred to this species. The two species can be differentiated by characters of the carapace, epistome, chelipeds and gonopods. Lectotypes are also designated for both species.